Efektifitas Senam Dengan Modul Dalam Mengurangi Dismenore Pada Remaja SMA Di Kota Surakarta - Yuyun Setyorini; Satino Satino (Poltekkes Kemenkes Surakarta, 2016)
Abstract: Dysmenorrhea, Adolescents, Reproductive Health Module. Dysmenorrhea is the most common gynecological problems experienced by women. Based on the research background mentioned above, can be formulated research question